3 Tesla magnetic resonance spectroscopy: cerebral gliomas vs. metastatic brain tumors. Our experience and review of the literature. (1st August 2013) - Caivano, R.; Lotumolo, A.; Rabasco, P.; Zandolino, A.; D'Antuono, F.; Villonio, A.; Lancellotti, M. I.; Macarini, L.; Cammarota, A.
Abstract : The aim of the present study is to report about the value of magnetic resonance spectroscopy (MRS) in differentiating brain metastases, primary high-grade gliomas (HGG) and low-grade gliomas (LGG). MRI (magnetic resonance imaging) and MRS were performed in 60 patients with histologically verified brain tumors: 32 patients with HGG (28 glioblastomas multiforme [GBM] and 4 anaplastic astrocytomas), 14 patients with LGG (9 astrocytomas and 5 oligodendrogliomas) and 14 patients with metastatic brain tumors. The Cho/Cr (choline-containing compounds/creatine–phosphocreatine complex), Cho/NAA (N-acetyl aspartate) and NAA/Cr ratios were assessed from spectral maps in the tumoral core and peritumoral edema. The differences in the metabolite ratios between LGG, HGG and metastases were analyzed statistically. Lipids/lactate contents were also analyzed. Significant differences were noted in the tumoral and peritumoral Cho/Cr, Cho/NAA and NAA/Cr ratios between LGG, HGG and metastases. Lipids and lactate content revealed to be useful for discriminating gliomas and metastases. The results of this study demonstrate that MRS can differentiate LGG, HGG and metastases, therefore diagnosis could be allowed even in those patients who cannot undergo biopsy.